Tradisi Ketuwinan pada Harmoni Sosial di Kalangan Masyarakat Desa Sarirejo, Kecamatan Kaliwungu - Syah Bunaya Nur Ana’im; Natal Kristiono (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the role of the Ketuwinan tradition in maintaining social harmony in the Sarirejo Village community and identify supporting and inhibiting factors in its implementation. This study uses a qualitative approach with an ethnographic type. Data were obtained through in-depth interviews with community leaders, indigenous residents, and immigrants, and supported by secondary data in the form of related literature and documents. Data analysis techniques were carried out through the stages of data reduction, data presentation, and interactive conclusion drawing to gain a deep understanding of the community's social practices. The results of the study indicate that the Ketuwinan tradition is still consistently implemented as a hereditary tradition that contains the values ​​of tolerance, solidarity, and togetherness. This tradition plays an important role in strengthening social relations between residents, both indigenous and immigrant communities. Although there are differences in participation levels, this condition does not cause social conflict due to the existence of mutual respect in community life. Supporting factors for this tradition include collective awareness, community openness, and the value of togetherness, while inhibiting factors include workload, limited time, and psychological factors. The research findings indicate that the Ketuwinan tradition can be a model for strengthening social harmony in the community amidst ongoing social change.